Autonomía económica y género en el sector rural de América Latina: Economic autonomy and gender in rural Latin America Systematic Review - Villafuerte-Pezo, Ana María; García-Pacheco de Mercado, Ruth Mercedes; Lescano-Lopez, Galia Susana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Economic autonomy allows women to be economically self-sufficient and make free decisions regarding their lives. The generation of their own income represents a symbolic and key element for empowerment, reinforcement of self-esteem, self-worth and reflection on their gender roles. Based on the application of the PRISMA methodology, a systematic review was carried out to identify the factors and strategies that explain the economic autonomy of women in rural areas of Latin America; highlighting the participation in productive projects and and entrepreneurship, access to microcredit, as well as the strengthening of cooperation and solidarity processes.